Climate policy and nonrenewable resources : the green paradox and beyond - Pittel, Karen, 1969-; Ploeg, Frederick van der, 1956-; Withagen, Cees, 1950- (CESifo seminar series., 2014)
Too rapidly rising carbon taxes or the introduction of subsidies for renewable energies induce owners of fossil fuel reserves to increase their extraction rates for fear of their reserves becoming worthless. Fossil fuel use is thus brought forward. The resulting acceleration of global warming and counter-productivity of well-intended climate policy has been coined the Green Paradox. This volume presents a range of studies extending the basic analysis to allow for clean energy alternatives, dirty energy alternatives, and the intricate strategic issues between different countries on the globe.